2007
DOI: 10.1128/jvi.01939-06
|View full text |Cite
|
Sign up to set email alerts
|

Novel β-Barrel Fold in the Nuclear Magnetic Resonance Structure of the Replicase Nonstructural Protein 1 from the Severe Acute Respiratory Syndrome Coronavirus

Abstract: The nonstructural protein 1 (nsp1) of the severe acute respiratory syndrome coronavirus has 179 residues and is the N-terminal cleavage product of the viral replicase polyprotein that mediates RNA replication and processing. The specific function of nsp1 is not known. Here we report the nuclear magnetic resonance structure of the nsp1 segment from residue 13 to 128, which represents a novel ␣/␤-fold formed by a mixed parallel/antiparallel six-stranded ␤-barrel, an ␣-helix covering one opening of the barrel, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
162
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(168 citation statements)
references
References 72 publications
5
162
1
Order By: Relevance
“…Structures for the nsp1 proteins of HCoV-229E and HCoV-NL63 were computed with Modeller software (Marti-Renom et al, 2000) using the solution structure of NSP1 13-128 from the SARS-CoV (PDB code 2HSX) as a template structure (Almeida et al, 2007). Sequence alignment of the nsp1 proteins from HCoV-229E, HCoV-NL63 and SARS-CoV was performed with the program ClustalW and refined manually.…”
Section: Bioinformaticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structures for the nsp1 proteins of HCoV-229E and HCoV-NL63 were computed with Modeller software (Marti-Renom et al, 2000) using the solution structure of NSP1 13-128 from the SARS-CoV (PDB code 2HSX) as a template structure (Almeida et al, 2007). Sequence alignment of the nsp1 proteins from HCoV-229E, HCoV-NL63 and SARS-CoV was performed with the program ClustalW and refined manually.…”
Section: Bioinformaticsmentioning
confidence: 99%
“…The nsp1 proteins of SARS-CoV and MHV promote host mRNA degradation and suppress host gene expression (Kamitani et al, 2006;Zust et al, 2007;Narayanan et al, 2008). Nuclear magnetic resonance (NMR) analysis revealed that SARS-CoV nsp1 has a novel b-barrel structure mixed with ahelixes (Almeida et al, 2007). More recently, SARS-CoV nsp1 was found to block host translational machinery function by binding to the ribosome small subunit (Kamitani et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nsp1SARS-CoV (2HSX; 2GDT); TGEV (3ZBD)Almeida et al (2007) and Jansson (2013) Nsp3 UB1 SARS-CoV (2GRI) ; MHV (2M0I)Serrano et al (2007) andKeane and Giedroc (2013) Nsp3 PL1 pro TGEV (3MP2) Wojdyla et al (2010) Nsp3 X-domain SARS-CoV (2ACF; 2FAV); HCoV 229E (3EWQ; 3EJG); IBV (3EWO; 3EJF; 3EKE); FCoV (3ETI; 3EW5) Saikatendu et al (2005), Egloff et al (2006), Xu et al (2009a), Piotrowski et al (2009) and Wojdyla et al (2009) Nsp3 SUD SARS-CoV (2W2G; 2WCT; 2KQV; 2KQW; 2JZF; 2RNK) Tan et al (2009), Johnson et al (2010a) and Chatterjee et al . (2002, 2003), Yang et al (2003), Tan et al (2005), Zhao et al (2008) and Xue et al (2008) Nsp7 SARS-CoV (1YSY; 2KYS) Peti et al (2005), Johnson et al (2010b) Nsp7 + 8 complex SARS-CoV (2AHM); FCoV (3UB0) Zhai et al (2005) and Xiao et al (2012) Nsp9 SARS-CoV (1UW7; 1QZ8); HCoV 229E (2J97) Sutton et al (2004), Egloff et al (2004) and Ponnusamy et al (1XAK; 1YO4) Nelson et al (2005) and Hänel et al (2006) orf9b SARS-CoV (2CME) Meier et al (2006) Spike RBD alone and in complex with receptor SARS-CoV (2GHV; 2AJF); HCoV NL63 (3KBH); PRCV (4F5C); MHV (3R4D); MERS-CoV (4L3N; 4KR0; 4KQZ; 4L72) Hwang et al (2006), Li et al, 2005a, Wu et al (2009), Reguera et al (2012), Peng et al (2011), Chen et al (2013a), Lu et al (2013) and Wang et al (2013) Spike fusion core SARS-CoV (1WYY; 2BEQ; 2BEZ; 1ZV7; 1ZVB; 1ZV8; 1ZVA; 2FXP; 1WNC); MHV (1WDF; 1WDG); HCoV NL63 (2IEQ) Duquerroy et al (2005), Supekar et al (2004), Deng et al (2006), Hakansson-McReynolds et al (2006), Xu et al, 2004b and Zheng et al (2006) Nucleocapsid-NTD IBV (2C86; 2GEC; 2BXX); HCoV OC43 (4J3K); SARS-CoV (2OFZ; 2OG3; 1SSK); MHV (3HD4) Jayaram et al (2006), Fan et al (2005), Chen et al (2013b), Saikatendu et al (2007), Huang et al (2004) and Grossoehme et al (2009) Nucleocapsid-CTD IBV (2CA1; 2GE7; 2GE8); SARS-CoV (2CJR; 2JW8; 2GIB) Jayaram et al (2006), Chen et al (2007), Takeda et al (2008), Yu et al (2006) S2m SARS-CoV (1XJR) Robertson et al (2004) Structures elucidated by nuclear magnetic resonance (NMR) techniques are indicated by a Protein Data Bank (PDB) code in italics.…”
mentioning
confidence: 99%
“…Nsp1 sequences are divergent between subgroups of betacoronavirus, and no sequence similarity between SARS-CoV nsp1 and betacoronavirus subgroup A nsp1 proteins could be identified using standard searching tools such as PSI-BLAST. Almeida et al (2006Almeida et al ( , 2007 determined the NMR structure of the nsp1 segment from residue 13 to 128 and also showed that the polypeptide segments of residues 1-12 and 129-179 are flexibly disordered (PDB ID 2GDT; 2HSX) . Residues 13-128 of nsp1 represents a novel ␣/␤-fold formed by a mixed parallel/antiparallel 6-stranded ␤-barrel, an ␣-helix covering one opening of the barrel, and a 3 10 -helix alongside the barrel (Fig.…”
Section: Structurementioning
confidence: 99%